2021
DOI: 10.3390/math9212716
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Finite-Difference Schemes for Two Nonlinear Schrödinger Equations Describing Frequency Tripling in a Medium with Cubic Nonlinearity: Competition of Invariants

Abstract: Two 1D nonlinear coupled Schrödinger equations are often used for describing optical frequency conversion possessing a few conservation laws (invariants), for example, the energy’s invariant and the Hamiltonian. Their influence on the properties of the finite-difference schemes (FDSs) may be different. The influence of each of both invariants on the computer simulation result accuracy is analyzed while solving the problem describing the third optical harmonic generation process. Two implicit conservative FDSs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is demonstrated that, to avoid the development of the nonphysical solution's instability, it is necessary to consider the spectral invariant for providing computer simulations. In [61,62], the comparison of the efficiency of several conservative and splitting FDSs is provided. In [61], conservative FDSs are constructed for the problem of femtosecond pulse propagation in an optical fiber, considering the time derivative of the medium nonlinear response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is demonstrated that, to avoid the development of the nonphysical solution's instability, it is necessary to consider the spectral invariant for providing computer simulations. In [61,62], the comparison of the efficiency of several conservative and splitting FDSs is provided. In [61], conservative FDSs are constructed for the problem of femtosecond pulse propagation in an optical fiber, considering the time derivative of the medium nonlinear response.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed FDSs preserve several invariants involving both the intensity profile of the beam and the phase distribution of the beam. In [62], for the set of 1D-coupled NLSEs, two conservative FDSs are constructed. Each of them preserves one of two differential problem's invariants (the energy's invariant or the Hamiltonian), while another is preserved with the second order of approximation.…”
Section: Introductionmentioning
confidence: 99%